(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
This research aims to analyze how to develop the legal certainty for health institution during the Covid-19 pandemic period. The method used in this research is the normative research method, which analyzes the related constitutional regulations and legal materials. In handling the impacts of the Covid-19 pandemic which leads to the weakening of the economy, the government has issued some economic stimuli which are not limited to direct cash aid to the impacted people, but also relaxation and restructurization programs for health institution and their business organs. The writer concludes that those things are not enough to cope with the bankruptcy which threatens the nation. Because of that, there needs to be restructurization agreements between the health institution. This is because until now, the Constitution on Bankruptcy and the Postponement of Debt Payment Obligations are the latest legislations which regulate the debtors and creditors’ relation regarding their financial obligations during a financial crisis during the period of the Covid-19 pandemic to protect the health institution.